THE EFFECT EXPERIENTIAL MARKETING OF ONLINE BUSINESS ON CONSUMPTION BEHAVIOR IN MUSLIM COMMUNITIES - Achmad Fajaruddin; Diva Rafifah Mutiara Muhammad (Journal of Islamic Economics and Philanthropy, 2021)
Internet is a global network that connects electronic media with other media. The conveniences offered by internet services have changed people's lives. It is what eventually led to the term of e-commerce/market-place as an online business.  Management has also become more thorough in determining its online business strategy, as there would be a lot of competition to increase customer satisfaction and loyalty. One solution to compete is to apply experiential marketing, which could stimulate customer experience to increase satisfaction and ultimately lead consumers to become loyal to a product or service. However, in consuming products as Muslim, we have to make sure what product we consume according to Islamic Principles. This paper aims to analyze the effect of experiential marketing on online business on Islam's consumption behavior, especially for the University of Darussalam Gontor for Girls collegian in Mantingan, Ngawi, East Java. The method used in this paper is multiple linear regression analysis, with a total sample of 342 respondents and the analysis tool uses Eviews7. This paper shows that the experiential marketing dimension consisting of sense, feel, think, act, and relate simultaneously has a significant influence on the principles of consumer behavior in Islam, which consists of the Syariah Principle, Quantity Principle, Priority Principle, Social Principle, and Environmental Rule. It is shown that online product and service providers can apply experiential marketing to increase customer satisfaction and loyalty.